1999
DOI: 10.1038/sj.onc.1202668
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a p23 caspase-cleaved form of p27[KIP1] involved in G1 growth arrest

Abstract: p27 [KIP1] (p27) is a cyclin dependent kinase inhibitor, involved in the negative regulation of G 1 progression in response to a number of anti-proliferative signals. In this study we show, in growing mouse hybridoma (7TD1) and human myeloma (U266) cell lines, that p27 is highly expressed but slightly upregulated when cells are arrested, regardless to the phases of the cell cycle. In contrast, the speci®c blockade of these cells in early G 1 phase reveals the induction of a protein of 23 kDa (p23) speci®cally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 53 publications
0
41
1
Order By: Relevance
“…In order to examine the sensitivities of the thymocytes to DNA damage, primary cultured thymocytes prepared from mice were irradiated with 5 Gy of g-radiation (Figure 2d). g-ray irradiation induced apoptosis in Pin1 þ /À and Pin1À/À thymocytes, indicated by DNA ladder formation and cleavage for caspase-3 activation, and p27 Kip1 cleavage (cleaved p27 Kip1 is produced by the caspases including caspase-3 (Loubat et al, 1999)). Interestingly, Cdk2 cleavage was specific to p53-expressing (Pin1 þ /À and Pin1À/À) thymocytes, and the level of cyclin A1 was significantly increased by g-ray irradiation in p53À/À and Pin1À/Àp53À/À thymocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to examine the sensitivities of the thymocytes to DNA damage, primary cultured thymocytes prepared from mice were irradiated with 5 Gy of g-radiation (Figure 2d). g-ray irradiation induced apoptosis in Pin1 þ /À and Pin1À/À thymocytes, indicated by DNA ladder formation and cleavage for caspase-3 activation, and p27 Kip1 cleavage (cleaved p27 Kip1 is produced by the caspases including caspase-3 (Loubat et al, 1999)). Interestingly, Cdk2 cleavage was specific to p53-expressing (Pin1 þ /À and Pin1À/À) thymocytes, and the level of cyclin A1 was significantly increased by g-ray irradiation in p53À/À and Pin1À/Àp53À/À thymocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In order to examine the effects of Pin1 and p53 deficiency on the sensitivity of thymocytes to DNA damage, primary cultured thymocytes were irradiated with 5 Gy of g-ray irradiation. Both Pin1 þ /Àp53 þ /À and Pin1À/Àp53 þ /À thymocytes showed apoptotic responses, including DNA ladder formation, caspase-3 activation, and fragmentation of RB and p27 Kip1 (Fattman et al, 1997;Loubat et al, 1999;Katsuda et al, 2002). In contrast, Pin1 þ /Àp53À/À and Pin1À/À p53À/À thymocytes showed lower sensitivities to g-rays, and caspase-3 activation and fragmentation of its substrate molecules were not observed.…”
Section: Discussionmentioning
confidence: 96%
“…To check this hypothesis, LNCaP cells were incubated for 24 h in 1.5% DMSO to arrest cells in G 0 /G 1 (Loubat et al, 1999). After the removal of DMSO, FBS was added to the arrested cells for 24 h in presence or not of metformin.…”
Section: Metformin Does Not Induce Apoptosismentioning
confidence: 99%
“…36 In a human myeloma cell line, after induction of G1 arrest by DMSO, p27kip1 cleavage preceded any evidence of apoptosis. 20 In B-CLL cells, the p23 fragment appeared as soon as 6 h after fludarabine exposure, when fewer than 10% cells had undergone apoptosis as evidenced by MTT and TUNEL assays. The first appearance of p23 truncated form was concomitant with the onset of PARP cleavage.…”
Section: Cdk4 Activity Appears Restricted To the Cytoplasmmentioning
confidence: 99%
“…Caspases participate in the cleavage of several cell cycle regulatory proteins such as retinoblastoma protein and the cdk inhibitors p21Cip1 and p27kip1. [18][19][20] To better define the cell cycle arrest observed in primary B-CLL, we examined the expression of various cyclin-dependent kinases and inhibitors. We observed that nearly all B-CLL cells expressed high levels of cyclin D2, cyclin E, cdk2, cdk4 as well as p27kip1.…”
Section: Introductionmentioning
confidence: 99%